Comparative Genomics, Evolution, and Drought-Induced Expression of Dehydrin Genes in Model Brachypodium Grasses - Maria Angeles Decena; Sergio Gálvez-Rojas; Federico Agostini; Ruben Sancho; Bruno Contreras-Moreira; David L. Des Marais; Pilar Hernandez; Pilar Catalán (Plants, 2021)
Dehydration proteins (dehydrins, DHNs) confer tolerance to water-stress deficit in plants. We performed a comparative genomics and evolutionary study of DHN genes in four model Brachypodium grass species. Due to limited knowledge on dehydrin expression under water deprivation stress in Brachypodium, we also performed a drought-induced gene expression analysis in 32 ecotypes of the genus’ flagship species B. distachyon showing different hydric requirements. Genomic sequence analysis detected 10 types of dehydrin genes (Bdhn) across the Brachypodium species. Domain and conserved motif contents of peptides encoded by Bdhn genes revealed eight protein architectures. Bdhn genes were spread across several chromosomes. Selection analysis indicated that all the Bdhn genes were constrained by purifying selection. Three upstream cis-regulatory motifs (BES1, MYB124, ZAT) were detected in several Bdhn genes. Gene expression analysis demonstrated that only four Bdhn1-Bdhn2, Bdhn3, and Bdhn7 genes, orthologs of wheat, barley, rice, sorghum, and maize genes, were expressed in mature leaves of B. distachyon and that all of them were more highly expressed in plants under drought conditions. Brachypodium dehydrin expression was significantly correlated with drought-response phenotypic traits (plant biomass, leaf carbon and proline contents and water use efficiency increases, and leaf water and nitrogen content decreases) being more pronounced in drought-tolerant ecotypes. Our results indicate that dehydrin type and regulation could be a key factor determining the acquisition of water-stress tolerance in grasses.